A New High Gain Active Switched Network-Based Boost Converter for DC Microgrid Application - Shima Sadaf (16875999) (2021)
This paper deals with an active switched inductor network-based high gain boost converter. By using less number of components in circuit topology, a higher gain in voltage can be attained at a small duty cycle value by using the proposed converter, which helps in reducing the switch voltage stress and conduction loss. In addition, it draws continuous input current, has lower diode voltage stress, and lower passive component voltage ratings. The operating principles and key waveforms in Continuous Conduction Mode (CCM) and Discontinuous Conduction Mode (DCM) are presented. Parameter design, power loss calculation, characteristics, and comparative study with other non-isolated converters have been presented. Finally, a 200W hardware prototype is constructed and the viability of the proposed converter is verified through the experimentally obtained results. Other Information Published in: IEEE Access License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1109/access.2021.3077055